Investigating the Role of the microRNA-34/449 Family in Male Infertility: A Critical Analysis and Review of the Literature - Pantos, Konstantinos; Grigoriadis, Sokratis; Tomara, Penelope; Louka, Ioanna; Maziotis, Evangelos; Pantou, Agni; Nitsos, Nikolaos; Vaxevanoglou, Terpsithea; Kokkali, Georgia; Agarwal, Ashok; Sfakianoudis, Konstantinos; Simopoulou, Mara (Frontiers in Endocrinology, 2021)
There is a great body of evidence suggesting that in both humans and animal models the microRNA-34/449 (miR-34/449) family plays a crucial role for normal testicular functionality as well as for successful spermatogenesis, regulating spermatozoa maturation and functionality. This review and critical analysis aims to summarize the potential mechanisms via which miR-34/449 dysregulation could lead to male infertility. Existing data indicate that miR-34/449 family members regulate ciliogenesis in the efferent ductules epithelium. Upon miR-34/449 dysregulation, ciliogenesis in the efferent ductules is significantly impaired, leading to sperm aggregation and agglutination as well as to defective reabsorption of the seminiferous tubular fluids. These events in turn cause obstruction of the efferent ductules and thus accumulation of the tubular fluids resulting to high hydrostatic pressure into the testis. High hydrostatic pressure progressively leads to testicular dysfunction as well as to spermatogenic failure and finally to male infertility, which could range from severe oligoasthenozoospermia to azoospermia. In addition, miR-34/449 family members act as significant regulators of spermatogenesis with an essential role in controlling expression patterns of several spermatogenesis-related proteins. It is demonstrated that these microRNAs are meiotic specific microRNAs as their expression is relatively higher at the initiation of meiotic divisions during spermatogenesis. Moreover, data indicate that these molecules are essential for proper formation as well as for proper function of spermatozoa per se. MicroRNA-34/449 family seems to exert significant anti-oxidant and anti-apoptotic properties and thus contribute to testicular homeostatic regulation. Considering the clinical significance of these microRNAs, data indicate that the altered expression of the miR-34/449 family members is strongly associated with several aspects of male infertility. Most importantly, miR-34/449 levels in spermatozoa, in testicular tissues as well as in seminal plasma seem to be directly associated with severity of male infertility, indicating that these microRNAs could serve as potential sensitive biomarkers for an accurate individualized differential diagnosis, as well as for the assessment of the severity of male factor infertility. In conclusion, dysregulation of miR-34/449 family detrimentally affects male reproductive potential, impairing both testicular functionality as well as spermatogenesis. Future studies are needed to verify these conclusions.